2000
DOI: 10.1002/1097-0339(200012)23:6<425::aid-dc14>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided fine-needle aspiration biopsy of the thyroid: Role of on-site assessment and multiple cytologic preparations

Abstract: Several studies have shown that ultrasound guidance can serve as a valuable aid in improving the diagnostic yield of fine‐needle aspiration (FNA) biopsy of thyroid nodules. In this study, we evaluated the combined impact of ultrasound‐guidance, rapid on‐site evaluation of FNA specimens, and different cytologic preparations (fresh and alcohol‐fixed smears, Millipore filter) and staining methods (Diff‐Quik and Papanicolaou stains) on the diagnostic yield of thyroid FNA. Ultrasound‐guided FNA was performed on 282… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 16 publications
4
106
0
5
Order By: Relevance
“…Although the unsatisfactory rate for thyroid biopsies reported in the literature is variable, there is general agreement that onsite evaluation results in higher adequacy rates, and some evidence suggests that the use of ultrasound guidance improves adequacy. 16,[24][25][26] Unsatisfactory rates in the range of 4% to 5% have been reported for freehand and ultrasound-guided FNA with onsite evaluation, whereas rates from 10% to 43% have been reported for centers without onsite evaluation. 25,27 We have observed that the performance of CB in conjunction with FNA is very useful in further improving adequacy rates, especially when CP are assessed on site for adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the unsatisfactory rate for thyroid biopsies reported in the literature is variable, there is general agreement that onsite evaluation results in higher adequacy rates, and some evidence suggests that the use of ultrasound guidance improves adequacy. 16,[24][25][26] Unsatisfactory rates in the range of 4% to 5% have been reported for freehand and ultrasound-guided FNA with onsite evaluation, whereas rates from 10% to 43% have been reported for centers without onsite evaluation. 25,27 We have observed that the performance of CB in conjunction with FNA is very useful in further improving adequacy rates, especially when CP are assessed on site for adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been proven that on-site adequacy evaluation can reduce inadequate samples significantly. 19,20 The issue regarding the number of follicular cells required for adequacy has been debated over the years; and, to date, no consensus has been reached. 2 Until a standardized, practical guideline is established, each individual cytopathologist will have to use criteria with which he or she is comfortable.…”
Section: -15mentioning
confidence: 99%
“…Thorough physical examination, multiple passes to cover all areas of interest, and ultrasound-guided aspiration may reduce sampling errors. 19,21 Errors caused by misinterpretation of cytologic findings in adequate samples are uncommon. Two major sources of such errors are cystic PCT and FN.…”
Section: -15mentioning
confidence: 99%
“…The role of ROSE has been explored in the endoscopic-guided FNAC of thyroid lesions, pancreatic masses, TBNA of mediastinal and lymph nodal masses, and lung cytology, while we have studied the impact of ROSE on yield of ultrasound-guided FNACs of hepatic lesions (2,8,9,11,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%